Desempenho operacional e custos da operação de subsolagem em área de implantação de eucalipto - Simões, Danilo [UNESP]; da Silva, Magali Ribeiro [UNESP]; Fenner, Paulo Torres [UNESP] (My University, 2011)
The knowledge of operating performance of agricultural machinery has become a crescent concern and of utmost importance since mechanized production costs are directly affected by the efficiency of the machine in the field. This study determined the operational performance and economy of a tractor in the subsoiling operation in function of slope classes. The analysis technique included a time and movement study and the economic analysis of the parameters operational cost, production cost and energy consumption. On the classes of slope evaluated, increasing the percentage of inclination of relief, lowered the operational performance and increased the production costs. The cost of fuel represented the greatest percentage among those that make up the operational cost.
Operational performance and costs of the subsoiling operation in eucalypt implantation area
Keywords: Efficiency; Eucalyptus; Forestry operations; Soil tillage